Pengaruh Brand Ambasador, Iklan Penjualan Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Chill Caffe Tumpang - Nadhifa, Nanda Ayu; Rachma, N.; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research aims to test and explain the influence of brand ambassador, seles advertising and product quality on customer purchasing decisions at chill caffe tumpang. This research is of the type explanatory research using a quantitative approach and using the slovin formula which obtained a total of ninety respondents. To solve the problems in the research, SPSS assistance was used to analyze various types of tests such as validity tests, normality test, F test, t test, multiple linear regression analysis and adjusted r2 coefficient of determination test the results of this research are that brand ambassadors, seles advertising and product quality simultaneously and partially influencer consumer purchasing decisions. Keywords: Brand Ambassadors, Seles Advertising, Product Quality, Purchasing Decisions.